Life-cycle unemployment, retirement, and parametric pension reform - Walter H. Fisher; Christian Keuschnigg (Institute for Advanced Studies (IHS), 2011)
This paper investigates the consequences of pension reform for life-cycle unemployment and retirement. We find that (i) improving actuarial fairness in pension assessment not only boosts old age participation but also reduces unemployment among prime age workers and raises welfare; (ii) strengthening the tax benefit link boosts life-cycle labor supply on all margins and welfare; (iii) excluding unemployment benefits from the pension assessment base reduces unemployment, encourages later retirement and boosts efficiency; and (iv) extending the calculation period favors employment of young workers, might possibly lead to more unemployment among older ones, encourages postponed retirement and most likely yields positive welfare gains.
Keywords: H55; J26; 330; pensions; tax benefit link; retirement; unemployment